The Kenotic Matrix of Reconciliation : Subverting Status and Domination in the Epistle to Philemon - Ramarolahy Patricia Josette; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
This article offers a theological, exegetical, and socio-ethical reading of the Epistle to Philemon through the interpretive lens of kenosis, arguing that Christian reconciliation is fundamentally grounded in a voluntary self-emptying modeled after Christ. Often marginalized within the Pauline corpus as a merely private correspondence, Philemon is reinterpreted here as a profound theological laboratory of reconciliation wherein human dependencies are transformed through the evangelical logic of fraternity, humility, and sacrificial service. Adopting an interdisciplinary methodology that integrates historical-critical exegesis, socio-rhetorical analysis, and Pauline systematic theology, this study highlights a intersecting threefold kenotic dynamic involving Paul, Philemon, and Onesimus. Paul, acting as apostle and mediator, voluntarily divests himself of his institutional prerogatives, choosing instead a pastoral posture grounded in agapē, fraternal persuasion, and vulnerable mediation. By identifying with Onesimus and assuming his financial liabilities, Paul embodies the downward trajectory of Christ the servant. Philemon, conversely, is summoned to transcend his legally protected rights as a Roman master to welcome Onesimus no longer as a reified commodity, but as an absolute brother in Christ. Concurrently, Onesimus consents to return voluntarily, entering into a posture of structural accountability and relational restoration. This triple kenotic matrix demonstrates that authentic Christian reconciliation (katallagē) cannot exist without a voluntary renunciation of power, privilege, and systemic structures of domination. The study further demonstrates that while Paul refrains from an explicit juridical condemnation of imperial slavery, the baptismal sociology promoted in the letter introduces a subversive theological dynamic capable of progressively deconstructing social hierarchies from within. Finally, the article outlines generative perspectives for contemporary moral theology, pastoral leadership, conflict mediation, and restorative justice practices, establishing kenosis as a permanent theological criterion for genuine reconciliation and ecclesial communion.